Reasons why physical and emotional state of interpreter may affect on the quality of simultaneous interpretation - Kutmonbekova, Gulasal Jaloliddin qizi (Science and Education, 2023)
This article is devoted to the emotional and physical state of the interpreter during simultaneous interpretation. Simultaneous interopretation has always been perceived as a type of oral translation, in which the translator, in conditions of acute shortage of time, perceiving the text in one language, issues its translation in another language. The article studies stress factors that have a psychological impact on the work of a simultaneous interpreter.